Roll-Cage’s Hollow-Tubing Specification Assessment for an Off-Road Buggy - Mohd Amir Shazwan, Hashim; Muhammad Izzat Nor, Ma'arof; Nur Qistina, Jamaludin; Lim, Khai Hen; Nurzaki, Ikhsan; Girma, Tadesse Chala (INTI International University, 2023)
For an off-road buggy car, the roll cage is one of the most important safety features which needs to be integrated in the overall chassis design. The structure must be able to provide protection to the driver under various load conditions – especially during roll-over. The objective of this study was to determine the optimal roll cage assembly’s hollow-tubing diameter for the INTI University’s off-road buggy. The BAJA SAE standard was followed in designing the roll-cage. Based on the BAJA SAE standard, comparisons were made between two (2) hollow-tubing which were 21.3mm and 26.9 mm in outer diameter and with similar wall thickness of 2.3mm. The CAD model was developed via the Inventor software and Finite Element Analysis (FEA) was conducted via the ANSYS software. The result showed that for frontal impact, side impact and roll-over, the pipe with the outer diameter of 26.9mm has higher values safety factor at 2.8; against 1.79 for the 21.3mm. This is due to the difference in second moment of inertia, where, a tubing with higher second moment of inertia, has higher bending strength and stiffness. Nonetheless, the 21.3mm hollow tubing is still a good option for selection if factors such as minimal production cost and vehicle’s mass are of priority. In accordance to the BAJA SAE standard, the safety factor for the roll-cage needs to be within the range of 1.5 to 2. Thus, the 26.9mm tubing is overdesigned and could be omitted. For future studies, other assessments such as material selection for the roll-cage could be conducted.